Augmented reality 3D cubes puzzle bingo game for the elderly - Lim, Woan Ning *; Lee, Yunli *; Anggoro, Ivan * (2019)
The pace of population aging is increasing dramatically over years. Living longer as well as living well is the goal of many people. Studies showed that mobile gaming can enhance the cognitive abilities and psychomotor skills of the elderly at the same time give the elderly sense of enjoyment and reduce the feeling of loneliness. Augmented reality technologies have been used to enhance traditional games and the results are positive. An Augmented Reality 3D cubes Puzzle Bingo game (ARPinGo) targeted the elderly was developed in this project by adapting the idea of rubik cubes and the puzzle and bingo board game features. The aim of this project is to gauge the response of the elderly towards the game and their acceptance of augmented reality technologies in mobile gaming. A total of 24 elderly members from D’Happy Club in Petaling Jaya, Malaysia had participated in this study. A quantitative approach based on the Technology Acceptance Model (TAM) is used in the survey. The outcome of this study would provide valuable input for future development of gaming application for the elderly.